The Luxury Market in Brazil Market Opportunities and Potential - Diniz, C.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The Luxury Market in Brazil provides a holistic and practitioners approach to luxury marketing in Brazil. The book analyses the key challenges and opportunities facing luxury brands, while providing an insight into the skills and competencies to develop and implement effective luxury marketing strategies that are specific to the market in question.
Keywords: International business enterprises; Marketing; Management; Industrial management; Cultural studies; International economics; Industrial procurement; International Business; Marketing; Innovation/Technology Management; Cultural Studies; International Economics; Procurement